Pengaruh Kompetensi, Independensi dan Etika Audit terhadap Kualitas Audit Pada Inspektorat Aceh - Zacki Qamal (Program Magister Akuntansi Unsyiah, 2015)
The study purposes of this study was to examine the influence of competence, independence and auditor ethics on audit quality of the Aceh Inspector institution, both jointly simoutltaneously and individually. The population in this study were all auditors at the Aceh Inspectorat Institution as many as 83 people, while the data sources in this study were primary data from questionnaire surveys in the form of structured statements. The results showed that auditor's competence, independence and ethics had a positive effect on the audit quality.KEYWORDS : Competence, Independence, Auditor Ethics, and Audit Quality